A study on non-stoichiometric p-NiOx/n-Si heterojunction diode fabricated by RF sputtering: Determination of diode parameters. (December 2016) - Grilli, Maria Luisa; Aydogan, Sakir; Yilmaz, Mehmet
Abstract: NiOx thin films were grown on n-Si substrates by radio frequency sputtering technique for the fabrication of a heterojunction p-n diode. X-ray diffraction, scanning electron microscope and atomic force microscope results revealed that NiOx films had nano sized polycrystalline nature. The X-ray energy dispersive analysis was used to determine elemental composition of the NiOx films. High quality vacuum evaporated silver (Ag) (ohmic) layer and nickel (Ni) (measurement electrode) dots were used to make contacts to the p-NiO x /n-Si heterojunction, in such a way that 8 Ni/p-NiO x /n-Si/Ag devices were fabricated. Current-voltage (I–V ) and capacitance-voltage ( C–V ) measurements of the p-NiO x /n-Si heterojunctions showed good diode characteristics and the average barrier height has been calculated as 0.652 eV. Highlights: NiOx thin film was grown by r.f sputtering. The structural and electrical properties have been evaluated. XRD, SEM, AFM, I–V and C–V measurements were used. p -NiOx / n -Si heterojunction diode parameters were determined.